Gastrointestinal Disorders in Cat due to Feed Mycotoxin Contamination - Sukmanadi, Mohammad; Sofyan, Miyayu Soneta (Universitas Airlangga, 2020)
This case reported about mycotoxin contamination on cat feed cause gastrointestinal disorders. A 5 y.o. male domestic short hair cat (Felix domesticus) was brought to the Animal Hospital, Universitas Airlangga with a history has been lethargic and disphagia for 2 days with vomiting a yellow fluid and diarrhea. Bowel movements, increasing in panting, and urination were examined. Observation in cat with gastrointestinal disorders for 5 days in animal hospital. Abnormal intestine and hepatomegaly based on x-ray were confirmed about mycotoxin contamination on cat food. Treatment for contamination on cat food was done by given protexin like probiotic to stimulate a villi intestinal growth and gastric condition. Itraconazole for antifungal to maintanace mycotoxin contamination was also considered. Our prescription was performed for our management treatment with gastrointestinal disoders. In advice, veterinarians should be giving information about the nutritional diet for a pet animal.